Optical wireless communications : system and channel modelling with MATLAB - Ghassemlooy, Zabih (Taylor & Francis, 2013)
"Incorporating MATLAB, this book provides a single resource for optical wireless communication systems based on the systems approach. It presents past and current research activities to illustrate optical sources, transmitters, detectors, and receivers used in optical wireless communications. The text covers both indoor and outdoor environments as well as how different factors, including various channel models, affect the system performance. The authors also discuss the emerging field of visible light communications and describe techniques for mitigating channel impact on the system performance using theoretical analysis and simulation. Other topics include hybrid optical and RF wireless systems"--